Assessing information literacy among freshmen students in the University of the Philippines - Otara, Lea O. (2002)
With a contemporary environment of rapid technological change proliferating information resources and a fast-changing era of information age, the need for an information literate society has been realized. In recognizing this, academic institutions have extensively responded to educational reforms and development programs. Part of this transformation, particularly in advancing information literacy, is greatly contributed by librarians or information specialists in collaboration with the faculty.